Allegiant - Roth, Veronica (Waterville, Maine : HarperCollins, 2013)
"When Tris and Tobias leave their faction-based society, their new reality is even more alarming than the one they left behind"--
Originally published in a slightly different form by Katherine Tegen Books in 2013.
Sequel to: Insurgent.
Keywords: Courage -- Fiction; Loyalty -- Fiction; Love -- Fiction; Science fiction; Large type books